PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - M. Zaeni Febrian; Laila Hayati; Junaidi; Amrullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of the Geogebra-assisted Creative Problem Solving (CPS) learning model on the problem-solving abilities of Class VIII students at MTs Al Aziziyah Putra Kapek Gunungsari for the 2023/2024 academic year. This quantitative research is of the Quasi Experimental Design type with a Posttest-Only Non-Equivalent Control Group Design. The population of this study were all students in class VIII MTs Al-Aziziyah Putra Kapek Gunungsari for the 2023/2024 academic year. The samples used were class VIII-Special and class VIII-A using purposive sampling technique. Data collection techniques include written tests and observation sheets. The results of the hypothesis test show that there is a difference in the average scores of the two classes, namely the class given the Geogebra-assisted Creative Problem Solving (CPS) learning model and the class given the direct learning model. Supported by the results of the effect size test, a value of was obtained, which is in the high category. This shows that there is a difference in the problem solving abilities of students taught using the Geogebra-assisted Creative Problem Solving (CPS) learning model and students taught using the direct learning model for Class VIII students at MTs Al Aziziyah Putra Kapek Gunungsari for the 2023/2024 academic year in the high category. In learning activities, classes that use the Geogebra-assisted CPS model look more active because students are able to explore their thinking creatively because it is supported by the stages in the CPS learning model so that students are able to develop their ideas and thoughts which results in their problem solving abilities increasing.